17th AIAA Computational Fluid Dynamics Conference 2005
DOI: 10.2514/6.2005-5231
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Aerodynamic Computations on Unstructured Grids Using a Newton-Krylov Approach

Abstract: A Newton-Krylov algorithm is presented for the compressible Navier-Stokes equations in three dimensions on unstructured grids. The algorithm uses a preconditioned matrix-free Krylov method to solve the linear system that arises in the Newton iterations. Incomplete factorization is used as the preconditioner, based on an approximate Jacobian matrix after the reverse Cuthill-McKee reordering of the unknowns. Approximate viscous operators that involve only the nearest neighboring terms are studied to construct an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The Jacobian is approximately factored with an incomplete lower upper factorization [30] based on the footprint of the Jacobian (ILU(k)), because incomplete multilevel ILU factorizations [31] and incomplete dual thresholds factorizations [31] were found to be much less effective, as also reported and observed by others [25,28,32]. ILU(k) implies that a zero entry in the Jacobian may only become a nonzero in the ILU when it is up to k positions away from an existing nonzero element in the Jacobian.…”
Section: Preconditioningmentioning
confidence: 83%
“…The Jacobian is approximately factored with an incomplete lower upper factorization [30] based on the footprint of the Jacobian (ILU(k)), because incomplete multilevel ILU factorizations [31] and incomplete dual thresholds factorizations [31] were found to be much less effective, as also reported and observed by others [25,28,32]. ILU(k) implies that a zero entry in the Jacobian may only become a nonzero in the ILU when it is up to k positions away from an existing nonzero element in the Jacobian.…”
Section: Preconditioningmentioning
confidence: 83%
“…In the threshold strategy, ILUTðP; sÞ, elements are dropped if they are smaller than s, and at most the P largest elements are kept in each row. Although the ILUTðP; sÞ strategy allows more precise control, it is much more expensive to form, and both Pueyo and Zingg [13] and Wong and Zingg [19] have demonstrated that the ILU(p) strategy is much more efficient in the current context.…”
Section: Preconditioningmentioning
confidence: 96%
“…In computations of two-dimensional flows, levels of fill between 2 and 4 are typically optimal. Lower values are preferred in three-dimensions [19,20]. In the present work, a value of p equal to 4 is used in all cases.…”
Section: Preconditionermentioning
confidence: 98%
See 2 more Smart Citations